Least Learned Competencies in Mathematics 8: Basis in Crafting Strategic Intervention Materials - Laña, G (Journal of Research and Investigation in Education, 2023)
This descriptive research study was conducted to determine and analyze the least learned competencies in Mathematics 8 from First Quarter to Fourth Quarter in Naguilian District, Division of La Union as basis for crafting K to 12 aligned Strategic Intervention Materials (SIMs). It also looked into the problems encountered in teaching Mathematics 8. Grade 9 learners and teachers were the respondents; the learners’ participants were selected through Slovin’s formula. In treating the gathered data mean, percentages, frequencies, and ranking were used. It found that there were eight (8) least learned competencies in all the quarters (first, second, third, and fourth) and the level of performance was fairly satisfactory. It was concluded that the least learned competencies were those that require higher order thinking skills. It was recommended that the crafted K to 12 aligned Strategic Intervention Material should be adopted by high school teachers in Naguilian District and other high school teachers in the province as an additional learning material to address the weaknesses of the learners along the identified least learned competencies in Mathematics 8.